Projecting Faculty Retirement: Factors Influencing Individual Decisions - Lozier, G. Gregory; Dooris, Michael J. (American Economic Review, 1991)
The impending elimination of mandatory retirement for tenured faculty on January 1, 1994 (Public Law 99-592, 1986), has raised the visibility of a number of questions about faculty retirement behavior. What are the factors that influence individual faculty members' retirement decisions? How important are financial and nonfinancial considerations? Why do faculty in private institutions work to a later age, on average, than their colleagues in public institutions? Are there other systematic (for example, genderor discipline-related) differences as well? This paper is an attempt to answer such questions about individual faculty retirement behavior. The paper utilizes data collected as part of a comprehensive national study that projected faculty retirements through the year 2003 for over 35,000 faculty at 101 doctoral research, comprehensive, and general baccalaureate institutions (see our 1990 paper). The discussion that follows uses data from that broader institutional survey and from a survey of 747 faculty members age 55 and over who had separated from this same set of 101 institutions. Among the information provided by the 518 usable responses were data on factors that influence faculty members' decisions regarding the appropriate time to retire.